Cycling Cross-Bridges Contribute to Thin Filament Activation in Human Slow-Twitch Fibers - López-Dávila, Alfredo Jesus; Chalovich, Joseph M.; Zittrich, Stefan; Piep, Birgit; Matinmehr, Faramarz; Málnási-Csizmadia, Andras; Rauscher, Anna Á.; Kraft, Theresia; Brenner, Bernhard; Stehle, Robert (Frontiers in Physiology, 2020)
It has been shown that not only calcium but also strong binding myosin heads contribute to thin filament activation in isometrically contracting animal fast-twitch and cardiac muscle preparations. This behavior has neither been studied in human muscle fibres nor animal slow-twitch fibres. Human slow-twitch fibres are of additional interest since they contain the same myosin heavy chain isoform as the human heart. To explore myosin induced activation of the thin filament in isometric contracting human slow-twitch fibres, the endogenous troponin complex was exchanged for a well characterized fast-twitch skeletal troponin complex labelled with the fluorescent dye IANBD (fsTn-IANBD). The effectively exchanged amount of troponin was ≈ 70% (n=8). Increasing the calcium concentration from relaxing (pCa 7.5) to saturating levels (pCa 4.5) induced maximal force development and changed emission intensity of fsTn-IANBD by 26.8 ± 1.2% (n=8). Pretreatment of fibres with the myosin inhibitor para-amino-blebbistatin (AmBleb) strongly inhibited force and significantly (p = 0.0007) decreased the calcium induced change in emission intensity to 18.4 ± 2.5% (n=8). Switching from isometric to isotonic contraction at pCa 4.5 induced a 28.7 ± 2.9% (n=8) change of emission intensity of fsTn-IANBD and AmBleb abolished this dynamic fluorescence change. Thus, we showed by two different approaches that decreasing the number of strong binding cross-bridges at saturating calcium concentration significantly reduces the activation of the thin filament in human slow-twitch fibres. The detected myosin contribution to activation resembles that previously reported in rat cardiac and rabbit fast-twitch muscle preparations. Additionally, applying this method to slow-twitch human fibres obtained from the soleus muscle of cardiomyopathy patients could contribute to understand how point mutations of the cardiac myosin head affect regulation of muscle contraction and how those alterations could be eventually corrected by pharmacological approaches.